Forty years of IKEA kitchens and the rise of a neoliberal control of domestic space. (May 2019) - Ledin, Per; Machin, David
This article uses a social semiotic approach to look at the representations and designs of kitchens in the IKEA catalogue from 1975 until 2016. The authors find a shift from function to lifestyle of the order observed by scholars of advertising. But using Fairclough's concepts of 'technologization' in Discourse and Social Change (1992) and Van Leeuwen's New Writing (2006) concept, they are able to dig deeper to show that there are four stages of kitchen that become, they argue, more and more codified, with increasing prescription over the meaning of space and also regarding what takes place there. Such coding aligns with the ideas, values and identities of neoliberalism: 'flexible', 'dynamic', 'creative', 'solutions' and 'self-management'. The authors show how the features of New Writing allow a suppression of actual causalities and context, and permit symbolic and indexical meanings to take over. Domestic life itself becomes technologized, coded and stripped down to a number of symbols and indexical meanings which assemble easily into the requirements of the neoliberal order.